“Desta água beberei” : entre milagres e festas no distrito de Águas de São João (GO) - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This research is structured with the objective of reflecting on the importance and contribution of different narratives to the identity constitution of Águas de São João. The district belongs to the municipality of Goiás-GO and borders the cities of Itapirapuã, Faina and Matrinchã. In the past, it gave way to a farm named São João da Gurita in the Piedade region. It gained notability, firstly, for the popularization of its sulphurous water sources, and around 1963, with the anual Feast of São João, in the month of July. As expressed in its name, Águas de São João carries the presence of two strong narratives that produced and still produce meaning, on the one hand the Festa de Praise to São João Batista and, on the other, the existence of Águas Sulfurosas, bringing in the local narrative cases relating to miracles and healing. We sought to understand the importance of these two elements, the presence of Christian influence and the narratives about miracles attributed to sulphurous waters, for the social and symbolic structuring of the district. A questioning is also developed regarding the constitution of the Area of Relevant Ecological Interest (ARIE), a natural heritage in which the clash between the “usufruct” of the space by the locals and environmental preservation is evident. The methodology adopted is divided into bibliographical research, interviews with inhabitants and people who had/have contact with the place, and the production of mental maps, through which the intention is to analyze the representation of the district itself through those who live in it. Finally, the final product will be a video, documentary, made with materials developed throughout the research, among which maps of the region and district, aerial and terrestrial images and reflections on the interviews carried out stand out. It is understood that the product will help to enhance educational activities, and may be a material used by teachers, students and anyone who intends to learn more about the district; and tourist attractions, opening the possibility of a prior survey of information for those who do not know.
“I will drink from this water” : between miracles and festivities in the district of Águas de São João (GO)
Keywords: Águas sulfurosas; Simbolismo; Paisagem; Monumento; Sulfuric waters; Symbolism; Landscape; Monument; CIENCIAS HUMANAS::HISTORIA